Analisis Faktor Hambatan Peserta Didik Terhadap Pelaksanaan Pembelajaran Daring (Studi Kasus: Kelas X Multimedia SMK National Media Center Malang) - Cristina Pravitasari; Satrio Hadi Wijoyo; Wibisono Sukmo Wardhono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Online learning is learning that uses technology that learners and educators are not limited by space or time. The learning from home policy during the coronavirus (Covid-19) pandemic has caused all educational institutions to carry out learning online. This study aims to identify the barrier factors and the magnitude of the obstacles experienced by students and their effects on the implementation of online learning. This study uses quantitative methods with descriptive and inferential statistical analysis. Collecting data using an online questionnaire based on the Likert scale which has been tested for validity and reliability. Validity test with Pearson product moment correlation and reliability test with Cronbach Alpha. The research subjects were students of class X Multimedia at SMK National Media Center Malang. The research sample is 20% of the population with a sample size of 37 students. The results showed that students' barriers were grouped into internal factors with an average resistance of 59.45% and external factors with an average resistance of 53.2%. Internal factors consist of understanding with an average resistance of 57.9% and a concentration with an average of 61% resistance. External factors consist of facilities with an average barrier of 51.4% and the environment with an average barrier of 55%. There is a partial influence between the factors of barriers to understanding and concentration on the implementation of online learning, while for facilities and the environment there is no partial effect. There is a simultaneous influence between these four factors on the implementation of online learning.